Canagliflozin treatment of Hispanic and non-Hispanic patients with type 2 diabetes in a US managed care setting. (2nd January 2016) - Chow, Wing; Buysman, Erin; Rupnow, Marcia F.T.; Aguilar, Richard; Henk, Henry J.
Abstract: Background: Hispanic/Latino (H/L) ethnicity is associated with higher prevalence of type 2 diabetes mellitus (T2DM) and more complications and comorbidities. Few studies of antihyperglycemic agents (AHAs) have compared H/L with non-H/L patients. Randomized controlled trials and observational studies have shown canagliflozin (CANA) is effective at lowering hemoglobin A1C (A1C). Objective: To describe characteristics and compare glycemic control between H/L and non-H/L patients with T2DM filling their first prescription for CANA. Methods: This retrospective cohort study examined healthcare claims for diabetic patients who filled ≥1 prescription for CANA between 1 April 2013 and 31 October 2013. We captured available demographic data; ethnicity was imputed as previously published. Clinical data included the Diabetes Complications Severity Index (DCSI), A1C values, and claims for any AHA, with 6 months of follow-up. Results: Our sample included 438 (11.4%) H/L individuals and 3408 (88.6%) non-H/L individuals; each cohort had 43% females. The H/L patients were younger (53 vs. 56 years, p  < 0.001) with higher mean baseline A1C (8.9% vs. 8.5%, respectively; p  = 0.028) compared to non-H/L patients. Mean DCSI was similar (H/L 0.92 vs. non-H/L 0.84, p  = 0.289) between cohorts. More H/L patients (25%) were taking ≥3 AHAs at the first CANA prescription fill (vs. 21% for non-H/L; p  = 0.044), most commonly metformin, followed by sulfonylureas, dipeptidyl peptidase-4 inhibitors, and basal insulin. Among patients with ≥2 fills for CANA, mean adherence (proportion of days covered) was slightly lower for H/L than non-H/L patients (0.77 vs. 0.80, p  = 0.003). From their respective baseline A1C values, reduction in A1C was significantly greater for H/L than non-H/L patients (1.1% vs. 0.8%; p  = 0.043). Conclusion: Compared with non-H/L patients, our H/L patients were younger and had higher mean baseline A1C. Significant improvement in glycemic control was observed for both cohorts, with greater improvement for H/L patients. Additional research is warranted, including longer follow-up and adjusting for possible confounding factors.